Release of chlorine from the slow pyrolysis of NaCl-loaded cellulose at low temperatures - Rahim, Usman; Gao, Xiangpeng; Wu, Hongwei (Elsevier, 2015)
This study reports the chlorine (Cl) release during the slow pyrolysis of NaCl-loaded cellulose in the temperature range of 150–400 °C, providing new data to better understand the low-temperature Cl release during biomass pyrolysis. The results show that the form and amount of Cl released during the slow pyrolysis of the NaCl-loaded cellulose strongly depend on pyrolysis temperature. Cl is mainly released as HCl (g) at temperatures ≤300 °C whereas it can be released in forms that are organically bound in heavy tar (termed as “tar-Cl”) at temperatures ≥350 °C. The release of both HCl (g) and total Cl (including gaseous HCl and tar-Cl) begins at 200 °C, reaches the corresponding maximum values (~53% for gaseous HCl and ~71% for total Cl) at 350 °C, and then levels off with further increasing temperature to 400 °C. The amount of organically bound Cl in solid residues after pyrolysis also increases from ~6% at 150 °C to ~36% at 300 °C, expressed as % of Cl in the solid residues. Further increasing temperature to 350–400 °C leads to the depletion of the organically bound Cl in the solid residues. Our data show that the interaction between Cl and cellulose organic structure is at least one of the mechanisms responsible for the release of HCl (g) and tar-Cl during biomass pyrolysis.